Tax refunds and income manipulation evidence from the EITC - Florian Buhlmann; Benjamin Elsner; Andreas Peichl (University College Dublin, UCD School of Economics, 2018)
Welfare programs are important in terms of reducing poverty, although they create incentives for recipients to maximize their income by either reducing their labor supply or manipulating their taxable income. In this paper, we quantify the extent of such behavioral responses for the Earned Income Tax Credit (EITC) in the US. We exploit the fact that US states can set top-up rates, which means that at a given point in time, workers with the same income receive different tax refunds in different states. Using event studies as well as a border pair design, we document that raising the state EITC leads to more bunching of self-employed tax filers at the first kink point of the tax schedule. While we document a strong relationship up until 2007, we find no effect during the Great Recession. These findings point to important behavioral responses to the largest welfare program in the US.
Keywords: H20; H24; 330; EITC; bunching; income manipulation